Efficacy of type and value of auditing opinion on time revelation of information - Tabar, Ramin Ehsani; Nia, Masood Taheri (Ciência e Natura, 2015)
The main goal of this research is surveying efficacy of type and value of variation of Auditing opinion on time revealing of accepted companies of Tehran commercial papers bourse Statistics society of this research is accepted companies in the Tehran commercial papers since (9002 to 9002) years, that content of sample after screen manner correspond 000companies. In this research have been used from boarding and incorporating data with fixed effects. Outcomes of analysis by some variant regression in the assurance level 29% shows that variation of Auditing opinion type and variation value of Auditing opinion type cause increase of on time revelation of companies financial reports.